2009
DOI: 10.1038/ijir.2009.15
|View full text |Cite
|
Sign up to set email alerts
|

Raising awareness for the diagnosis and treatment of erectile dysfunction in patients with high risk to develop ED

Abstract: Prevalence of erectile dysfunction (ED) increases with age and is associated with chronic comorbidities, such as diabetes and hypertension. Even so, ED is underdiagnosed and undertreated. This study investigated the effect of raising awareness of ED diagnosis and treatment in a community setting by physicians' education. Thirty-nine primary care physicians participated in lectures by a trained sexologist, and 20 of them also received computerized lists of their high-risk patients. We matched a control group of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…9 For that reason, raising awareness and educating physicians who treat sexual dysfunction are important, as enquiries with regard to sexual functions should be routinely carried out by clinicians. [10][11][12] The treatment of ED has been generally ignored by family practitioners. Possible explanations include family practitioners being unaware of the true prevalence of the problem, the sensitivity of raising the problem and the lack of time and lack of training of family practitioners to discuss the subject with their patients.…”
Section: Discussionmentioning
confidence: 99%
“…9 For that reason, raising awareness and educating physicians who treat sexual dysfunction are important, as enquiries with regard to sexual functions should be routinely carried out by clinicians. [10][11][12] The treatment of ED has been generally ignored by family practitioners. Possible explanations include family practitioners being unaware of the true prevalence of the problem, the sensitivity of raising the problem and the lack of time and lack of training of family practitioners to discuss the subject with their patients.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, ED can be viewed as a barometer of overall cardiovascular risk and as an early and potentially predictive index of systemic cardiovascular target‐organ damage, even in otherwise healthy men with ED (Kaiser et al, 2004; Pritzker, 1999). Reciprocally, the presence of some of these factors (e.g., CAD, diabetes, hypertension, smoking) should prompt inquiries about sexual function (Azuri, Gelerenter, Dushinat, Friedman, & Kokia, 2009).…”
mentioning
confidence: 99%
“…Articles were excluded if they did not contain the key terms: ED, diagnosis, treatment, and IIEF-5 together in the study. A total of 15 relevant articles including: five clinical practice guidelines (CPGs) (Canadian Guidelines Towards Optimized Practice [TOP], 2010; Hatzimouratidis et al, 2010;Kimoto et al, 2008;Montague et al, 2009;Qaseem et al, 2009), four systematic reviews (Cappelleri & Rosen, 2005;Markou, Perimenis, Gyftopoulos, Athanasopoulos, & Barbalias, 2004;Ruiz-Aragon, Marquez-Pelaez, & Romero, 2010;Tsertsvadze et al, 2009), three RCTs (Azuri, Gelerenter, Dushinat, Friedman, & Kokia, 2009;Hwang et al, 2010;Shabsigh et al, 2010), two prospective cohort studies (Hakim et al, 2002;Ponholzer et al, 2005), and one non-experimental descriptive study (Baldwin, Ginsberg, & Harkaway, 2003) were reviewed.…”
Section: Search Strategymentioning
confidence: 99%
“…The authors found that while awareness of having ED was minimal, most of the participants with risk factors had a IIEF-EF score indicating some degree of ED and recommend that patients with risk factors be evaluated. Azuri, Gelerenter, Dushinat, Friedman, and Kokia (2009) used a randomized controlled trial to examine the outcome of increasing understanding of the diagnosis and treatment of ED in a community environment using physicians' education. A sample size of 1,959 men in two intervention groups and 1,903 men in the control group along with a random sample of 40 primary care physicians in both the intervention and control groups were the focus of this study.…”
Section: Review Of Literaturementioning
confidence: 99%
See 1 more Smart Citation